1994
DOI: 10.1017/s0033291700027756
|View full text |Cite
|
Sign up to set email alerts
|

Bulimia comorbidity in the general population and in the clinic

Abstract: SynopsisThis study compares rates of comorbidity of lifetime psychiatric disorder in a clinical sample of women with bulimia, with general population base rates, and with rates of comorbidity among bulimic women in the general population. Eighty-four per cent of the clinical sample of bulimic women had a lifetime affective disorder, and 44% a lifetime alcohol or drug disorder. These rates of disorder were significantly higher than the base rates in the general population. Bulimic women in the general populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
2
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 28 publications
5
67
2
3
Order By: Relevance
“…These results are again generally consistent with those reported in previous population-based studies for anorexia nervosa (Garfinkel et al 1996), bulimia nervosa (Kendler et al 1991;Bushnell et al 1994;Garfinkel et al 1995;Rowe et al 2002), binge eating behavior ( Several findings in this study are particularly noteworthy. First, we found that anorexia nervosa displayed a significantly shorter lifetime duration and lower 12-month persistence, as well as lower overall levels of comorbidity, than either bulimia nervosa or binge eating disorder.…”
Section: Discussionsupporting
confidence: 93%
“…These results are again generally consistent with those reported in previous population-based studies for anorexia nervosa (Garfinkel et al 1996), bulimia nervosa (Kendler et al 1991;Bushnell et al 1994;Garfinkel et al 1995;Rowe et al 2002), binge eating behavior ( Several findings in this study are particularly noteworthy. First, we found that anorexia nervosa displayed a significantly shorter lifetime duration and lower 12-month persistence, as well as lower overall levels of comorbidity, than either bulimia nervosa or binge eating disorder.…”
Section: Discussionsupporting
confidence: 93%
“…All the subjects showed a lifetime comorbidity with at least one axis I disorder, and 73.1% of them with more than one other mental disorder, which is higher, compared with other surveys [19,39,40,41,42,43], however, consistent in reporting anxious and depressive disorders as the most frequent comorbid conditions [19, 20, 39,40,41,42,43,44,45]. The high level of comorbidity probably explains the high percentage of subjects who consulted a doctor and received treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Apart from information on the prevalence and distribution of these disorders, community surveys may have significant relevance for studying the clinical features of ED patients, which often differ from those observed in clinical settings [19,20,21]. Since clinical samples are likely to be selected on the basis of a greater severity, community samples may add information on the natural course and outcome of these disorders [22].…”
Section: Introductionmentioning
confidence: 99%
“…46 Women who seek treatment for eating disorders are more likely to have comorbid conditions, including affective disorders, 47 and may not be truly representative of the population of individuals with eating disorders. Consequently, the first aim of the current study was to examine depression during pregnancy and postpartum in a large, population-based sample of women, controlling for a previous lifetime history of MDD.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…High rates of comorbidity between eating disorders and major depressive disorder (MDD) have been identified in numerous studies. [12][13][14][15][16][17][18][19] However, much less is known about depression during pregnancy and the postpartum period among women with eating disorders. In addition, some women have reported that their eat-ing disorders began in the postpartum period, as they attempted to lose weight gained during pregnancy.…”
Section: Introductionmentioning
confidence: 99%